Pengaruh Budaya Ghasab Terhadap Hasil Belajar Siswa MAN 4 Jombang - Zain, Rizal Fadhlan; Fauzi, Agus Machfud (Paradigma, 2024)
Abstract Ghasab culture is a phenomenon that is often encountered, especially in Islamic boarding school environments. Ghasab is a deviant culture and has a negative impact on the perpetrators and victims. One environment that cannot escape this culture is madrasah schools because they are located in Islamic boarding school environments. Because it has a negative impact, one of the initial hypotheses is that students’ learning outcomes have decreased. The researcher’s aim in taking this theme is to determine the influence of ghasab culture on student learning outcomes. The research is located at MAN 4 Jombang which is steped in Islamic boarding school teachings. This research uses quantitative methods to determine the level of significance betwen 2 variables. The variables in question are ghsab culture as variable X and learning outcomes as variable Y. In collecting data, research used a questionnaire distributed to respondents. The data obtained will then be processed into tabulation so that the numbers of X and Y can be known. The next stage is the correlation test and reliability test. To find the significance level, researchers used Pearson’s product moment and t test. After the data was processed, the results of the correlation test appeared as shown in Table 4.5, recording a calculated r value of 0.239 betwen the ghasab culture instrument and student learning outcomes. Apart from that, the significance value (Sig. 2-tailed) obtained is 0.00. This finding shows that the significance value (Sig. 2-tailed) is below the predetermined ? value, namely 0.05. Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, which shows that there is a significant influence betwen ghasab culture on the learning outcomes of MAN 4 Jombang students. Keywords: Ghasab Culture, Learning Outcomes, Social Action, Significance, New Culture Abstrak Budaya Ghasab merupakan sebuah fenomene yang sering di jumpai terutama di lingkungan pesantren. Ghasab termasuk budaya yang menyimpang dan memiliki dampak negatif bagi para pelakunya maupun korban. Salah satu lingkungan yang tak luput dari budaya ini adalah di sekolah madrasah karena berada di lingkungan pondok pesantren. Karena memiliki dampak yang negatif, Hipotesis awal salah satunya adalah hasil belajar para siswa yang menglami penurunan. Tujuan peneliti mengambil tema ini adalah untuk mengetahui pengaruh budaya ghasab terhadap hasil belajar siswa. Penelitian yang berlokasi di MAN 4 Jombang yang kental akan ajaran pondok pesantren. Penelitian ini menggunakan metode kuantitatif untuk mengetahui tingkat signifikansi antara 2 variabel. Variabel yang dimaksud adalah budaya ghsab sebagai variabel X dan hasil belajar sebagai variabel Y. Dalam pengumpulan data meneliti menggunakan kuisioner yang disebar kepada para responden. Data yang diperoleh lalu akan diolah menjadi tabulasi sehingga jumlah X dan Y dapat diketahui. Tahap selanjutnya yaitu uji korelasi dan uji reliabilitas. Untuk menemukan tingkat signifikansi peneliti menggunakan product moment Pearson dan uji t hitung. Setelah data diolah muncul hasil uji korelasi yang ditunjukkan dalam hasil olah data mencatat nilai r hitung sebesar 0,239 antara instrumen budaya ghasab dan hasil belajar siswa. Selain itu, nilai signifikansi (Sig. 2-tailed) yang diperoleh adalah 0,00. Temuan ini menunjukkan bahwa nilai signifikansi (Sig. 2-tailed) berada di bawah nilai ? yang telah ditentukan, yaitu 0,05. Oleh karena itu, hipotesis nol (H0) ditolak dan hipotesis alternatif (H1) diterima, yang menunjukkan adanya pengaruh signifikan antara budaya ghasab terhadap hasil belajar siswa MAN 4 Jombang. Kata kunci: Budaya Ghasab, Hasil Belajar, Tindakan Sosial, Budaya Baru